2022
DOI: 10.1371/journal.pone.0277986
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary team healthcare professionals’ perceptions of current and optimal acute rehabilitation, a hip fracture example A UK qualitative interview study informed by the Theoretical Domains Framework

Abstract: Objective To understand multidisciplinary team healthcare professionals’ perceptions of current and optimal provision of acute rehabilitation, perceived facilitators and barriers to implementation, and their implications for patient recovery, using hip fracture as an example. Methods A qualitative design was adopted using semi-structured telephone interviews with 20 members of the acute multidisciplinary healthcare team (occupational therapists, physiotherapists, physicians, nurses) working on orthopaedic wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Effective communication was believed to mitigate concerns about falling and activity restriction by attending medical concerns, increasing access to formal care, providing positive feedback, advice on health consequences, and strategies for safe mobility and ADL engagement [ 43 47 ]. Effective communication strategies have been considered crucial by clinicians for engaging patients and improving outcomes after hip fracture [ 62 , 63 ]. One cross-sectional study of low quality suggested no association between the use of multiple medications and concerns about falling, even though this may reflect frailty and was associated with concerns about falling after hip fracture in a recent study [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Effective communication was believed to mitigate concerns about falling and activity restriction by attending medical concerns, increasing access to formal care, providing positive feedback, advice on health consequences, and strategies for safe mobility and ADL engagement [ 43 47 ]. Effective communication strategies have been considered crucial by clinicians for engaging patients and improving outcomes after hip fracture [ 62 , 63 ]. One cross-sectional study of low quality suggested no association between the use of multiple medications and concerns about falling, even though this may reflect frailty and was associated with concerns about falling after hip fracture in a recent study [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Theoretical Domains Framework (TDF) provides a useful ‘first step’ toward recognizing and classifying barriers and facilitators that impact implementation of services for Medicaid recipients (Cane, O’Connor, & Michie, 2012). By structuring qualitative data as barriers and facilitators, the TDF permits for targeted intervention (Guerra, Lambe, Manolova, Sadler, & Sheehan, 2022). Comprised of 14 validated domains (knowledge; skills; social/professional role and identity; beliefs about capabilities; optimism; beliefs about consequences; reinforcement; intention; goals; memory, attention, and decision processes; environmental context and resources; social influences; emotion; and behavioral regulation) to help organize social, cognitive, environmental, and affective influences on one’s behavior, the TDF has previously been applied in qualitative health research to determine healthcare professionals’ perceptions across a variety of settings (Guerra et al, 2022; Pearse, Keogh, Rickard, & Fung, 2021).…”
Section: A Reproductive Justice Approachmentioning
confidence: 99%
“…By structuring qualitative data as barriers and facilitators, the TDF permits for targeted intervention (Guerra, Lambe, Manolova, Sadler, & Sheehan, 2022). Comprised of 14 validated domains (knowledge; skills; social/professional role and identity; beliefs about capabilities; optimism; beliefs about consequences; reinforcement; intention; goals; memory, attention, and decision processes; environmental context and resources; social influences; emotion; and behavioral regulation) to help organize social, cognitive, environmental, and affective influences on one’s behavior, the TDF has previously been applied in qualitative health research to determine healthcare professionals’ perceptions across a variety of settings (Guerra et al, 2022; Pearse, Keogh, Rickard, & Fung, 2021). Previous work has documented the TDF’s usefulness for the synthesis of qualitative evidence related to ‘policy-urgent’ questions (Shaw, Holland, Pattison, & Cooke, 2016), making Florida’s Medicaid reimbursement process an area ripe for exploration.…”
Section: A Reproductive Justice Approachmentioning
confidence: 99%
“…Studies about provision of acute rehabilitation for hip fracture with clinical leaders and physiotherapists have highlighted the importance of communication between professionals and patients in rehabilitation for hip fracture 12 13. Similarly, a recent interview-based study by Guerra and colleagues with healthcare professionals explored acute rehabilitation and implementation 14. The study found that communication and collaboration are central to provision of effective rehabilitation and that organisational constraints are seen as a barrier to such provision.…”
Section: Introductionmentioning
confidence: 99%